The Effects of Active Galactic Nuclei Feedback on the Lyα Forest Flux Power Spectrum - Megan Taylor Tillman; Blakesley Burkhart; Stephanie Tonnesen; Simeon Bird; Greg L. Bryan (The Astrophysical Journal)
We study the effects of active galactic nuclei (AGN) feedback on the Ly α forest 1D flux power spectrum (P1D). Using the Simba cosmological-hydrodynamic simulations, we examine the impact that adding different AGN feedback modes has on the predicted P1D. We find that, for Simba , the impact of AGN feedback is most dramatic at lower redshifts ( z  < 1) and that AGN jet feedback plays the most significant role in altering the P1D. The effects of AGN feedback can be seen across a large range of wavenumbers (1.5 × 10 ^−3  <  k  < 10 ^−1 s km ^−1 ) changing the ionization state of hydrogen in the IGM through heating. AGN feedback can also alter the thermal evolution of the IGM and thermally broaden individual Ly α absorbers. For the Simba model, these effects become observable at z  ≲ 1.0. At higher redshifts ( z  > 2.0), AGN feedback has a 2% effect on the P1D for k  < 5 × 10 ^−2 s km ^−1 and an 8% effect for k  > 5 × 10 ^−2 s km ^−1 . We show that the small-scale effect is reduced when normalizing the simulation to the observed mean flux. On large scales, the effect of AGN feedback appears via a change in the IGM temperature and is thus unlikely to bias cosmological parameters. The strong AGN jets in the Simba simulation can reproduce the z  > 2 Ly α forest. We stress that analyses comparing different AGN feedback models to future higher precision data will be necessary to determine the full extent of this effect.